2022
DOI: 10.1039/d2tc00075j
|View full text |Cite
|
Sign up to set email alerts
|

Stable and wide-wavelength tunable luminescence of CsPbX3 nanocrystals encapsulated in metal–organic frameworks

Abstract: Lead-halide perovskite nanocrystals (PeNCs) possess attractive linear and nonlinear optical properties. However, further adjusting their linear and nonlinear optical properties in a facile way remains great challenge due to the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…[1][2][3][4][5] Therefore, they have attracted wide attention in many fields such as photovoltaics, 6,7 light-emitting diodes (LEDs), photodetectors, and biological imaging. [8][9][10][11][12][13][14][15] The general structure formula of LHP NCs is ABX 3 (A = Cs + /CH 3 NH 3 + /CH 3 (NH 2 ) 2 + , B = Pb 2+ , X = Cl À /Br À /I À ). In the case of CH 3 NH 3 + /CH 3 (NH 2 ) 2 + as the A cation, this material is called organic-inorganic hybrid LHP NCs with excellent photoelectric properties, such as large optical absorption coefficient, low defect density, and long carrier diffusion length.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Therefore, they have attracted wide attention in many fields such as photovoltaics, 6,7 light-emitting diodes (LEDs), photodetectors, and biological imaging. [8][9][10][11][12][13][14][15] The general structure formula of LHP NCs is ABX 3 (A = Cs + /CH 3 NH 3 + /CH 3 (NH 2 ) 2 + , B = Pb 2+ , X = Cl À /Br À /I À ). In the case of CH 3 NH 3 + /CH 3 (NH 2 ) 2 + as the A cation, this material is called organic-inorganic hybrid LHP NCs with excellent photoelectric properties, such as large optical absorption coefficient, low defect density, and long carrier diffusion length.…”
Section: Introductionmentioning
confidence: 99%
“…Cesium lead halide perovskites (CsPbX 3 , where X = Cl, Br, I), with adjustable band gaps covering the entire visible region, are promising for various optoelectronic devices. The perovskite crystal can be regarded as a combination of CsX and PbX 2 (X = Cl, Br, I). According to the connectivity of the octahedron (PbX 6 ), they can form different configurations (Cs n PbX 2+ n ), which are regarded as two-dimensional (2D), one-dimensional (1D), and zero-dimensional (0D) perovskites. Among them, the 0D perovskites (Cs 4 PbX 6 ) exhibit extraordinary and valuable properties that are notably different from the regular three-dimensional (3D) perovskites (CsPbX 3 ) due to the strong quantum confinement and site isolation .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, CsPbI 3 crystals are black, CsPbBr 3 crystals are orange, and CsPbCl 3 crystals are pale yellow, while Cs 4 PbX 6 (X = I, Cl, or Br) crystals have no color. In addition, CsPbX 3 shows photoconductivity properties and exhibits maximal spectrum sensitivity towards violet (CsPbCl 3 ), blue to green (CsPbBr 3 ), and red (CsPbI 3 ) [ 86 , 87 ]. Many researchers have reported that CsPbX 3 perovskite is a good light absorber ( Figure 2 ) due to its high absorption coefficient [ 88 , 89 , 90 , 91 , 92 ].…”
Section: Physical and Optical Characteristics Of Qdsmentioning
confidence: 99%